Mapping myeloid cell function: Spatial diversity in tumor and neuronal microenvironment - Villa, Giulia; Delev, Daniel; Heiland, Dieter Henrik (Cancer Cell, 2024)
In this issue of Cancer Cell, Zhong et al. explore the dual role of TREM2 in glioblastoma-associated myeloid cells, demonstrating its function in promoting inflammation at the tumor-neural interface and suppression within the tumor core, influenced by the local microenvironment. These findings open up promising prospects for advancements in neuro-oncological immunotherapy.
CRIS-Team Scopus Importer:2024-06-14